Methamphetamine and-or morphine : acute changes in striatal dopaminergic transmission and neurotoxicity - Pereira, Frederico Guilherme de Sousa da Costa (2007)
Tese de doutoramento em Ciências Biomédicas apresentada à Fac. de Medicina de Coimbra